2022
DOI: 10.1186/s13104-022-06120-1
|View full text |Cite
|
Sign up to set email alerts
|

Hearing loss and the COVID-19 pandemic

Abstract: Objective Hearing loss is an important public health problem. Its causes vary, including infections, noise, and aging. The first wave of the COVID-19 pandemic occurred in April 2020 in Japan. During the pandemic, people were urged to stay at home and drastically changed their lifestyles. This study aimed to examine hearing loss before and during the pandemic. The prevalence during the pandemic after April 2020 was compared for the period in 2019. Study subjects were those who received health ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
0
4
0
1
Order By: Relevance
“… 15 A meta-analysis showed that the rate of hearing loss in patients with COVID-19 was 3.1%. 67 A systematic review on all patients undergoing PTA conducted by Fancello et al, showed unilateral SNHL in 36 patients and bilateral SNHL in 27 patients. Hearing loss ranged from mild to moderate in 58.7%, from moderate to severe in 4.8%, and from severe to profound in 36.5% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“… 15 A meta-analysis showed that the rate of hearing loss in patients with COVID-19 was 3.1%. 67 A systematic review on all patients undergoing PTA conducted by Fancello et al, showed unilateral SNHL in 36 patients and bilateral SNHL in 27 patients. Hearing loss ranged from mild to moderate in 58.7%, from moderate to severe in 4.8%, and from severe to profound in 36.5% of the patients.…”
Section: Discussionmentioning
confidence: 99%
“…That said, a substantial amount of COVID-19-related hearing loss literature deals with symptoms only, self-reported by a variable proportion of infected patients (up to 50%) (Elibol, 2021;AlJasser et al, 2022;Almishaal and Alrushaidan, 2022;Deva et al, 2022;Savtale et al, 2022;Vielsmeier et al, 2022). These reports often did not quantify or qualify the hearing (Wagatsuma et al, 2022), and therefore were limited in their contributions to the literature (Almufarrij and Munro, 2021;Trott et al, 2022). It is also important to consider that hearing loss may have been underreported by patients during the pandemic, as many patients avoided hospitals (by choice or not).…”
Section: Discussionmentioning
confidence: 99%
“…especialmente en frecuencias altas . La prevalencia de hipoacusia en nuestro estudio podría deberse al uso prolongado y a volumen alto de auriculares durante la pandemia de COVID-19, cuando la virtualidad aumentó signi cativamente el tiempo de uso de estos dispositivos (18,19) .…”
Section: Sexounclassified